869 Understanding medical students' perceived barriers to examining paediatric patients. (17th August 2022) - Yunus, Azedah; Jones, Erin; Kelly, Alison; Ottman, Mia
Abstract : Aims: 1. Understand common barriers to medical students examining paediatric patients 2. Identify any means to help students overcome these barriers to ensure they get the most out of their paediatric placement 3. Evaluate how useful students find the weekly bedside teaching sessions with the clinical teaching fellows Methods: Students at University of Bristol undergo a 6-week paediatric placement in which they are encouraged to examine as many paediatric patients on their own as possible to increase their confidence and bedside skills. We noted that students were not examining as many paediatric patients as expected. To understand this we devised an online questionnaire to send to three cohorts of students (n=45). The questionnaire asked students about their level of confidence examining children before and after their paediatric placement and invited them to explain any barriers they faced when trying to examine children and any suggests for support the education team could provide. Results: We received 16 responses to our questionnaire. Average student reported confidence examining paediatric patients at the start of their placement was 2.6 on a Likert scale where 5 represents 'very confident'. This improved to 3.6 at the end of their placement. The mean number of paediatric patients examined by each student was 26. Students identified that the primary barrier to examining more patients was perceived lack of paediatric knowledge (n=4) as well as a lack of confidence (n=4). Students reported concern they would upset patients or parents. They also describe feeling their paediatric placement is too short and that they have insufficient time on the wards alongside other timetabled elements. When asked how the paediatric education team could help overcome these barriers students suggested more bedside teaching sessions (n=4), more didactic teaching to feel confident with paediatric presentations (n=3) and more time to examine patients. Students also suggested educating parents on the presence of medical students and having a list of patients who are willing to see medical students. Conclusion: Medical students lack the confidence needed to examine children as part of their paediatrics placement. This confirms a similar published report that novice students on adult placements also reporting lack of confidence as a key barrier to examining patients. 1 With much less time spent as a student in paediatrics compared to adults it is much more important to address this issue in paediatrics quickly. There is only a modest increase in confidence levels despite six bedside teaching sessions delivered during the placement, and suggests more work to be done to improve student confidence. Based on the information we have gathered we have implemented an examination record sheet to support students struggling to examine patients. We are also considering how to use existing clinical IT systems to include information about suitable patients for medical students. Reference: Medical Education, Barrett, Trumble and McColl